Critical Success Factors For Implementing E-Procurement: A Case Study On SKF Bearing Industries (M) Sdn Bhd - Vinayan, Gowrie (2002)
This paper focuses on identifying critical success factors of SKF Bearing Industries (M) sdn Bhd (SKF) that enable successful implementation and utilization of sound e-procurement solutions. This study will lead to formulation of a strategy for E-procurement, which includes, opportunities to reduce the costs of goods and services through aggregating purchasing volume and to further streamline purchasing procedures.